2014
DOI: 10.1182/blood-2013-08-521914
|View full text |Cite
|
Sign up to set email alerts
|

MLN4924, an NAE inhibitor, suppresses AKT and mTOR signaling via upregulation of REDD1 in human myeloma cells

Abstract: • Blockade of NAE and bortezomib induces phosphatidylinositol 3-kinase/ mTOR inhibition.• NAE inhibition and bortezomib combined induce synergistic plasma cell apoptosis.The function and survival of normal and malignant plasma cells depends on the elaborately regulated ubiquitin proteasome system. Proteasome inhibitors such as bortezomib have proved to be highly effective in the treatment of multiple myeloma (MM), and their effects are related to normal protein homeostasis which is critical for plasma cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 33 publications
4
58
2
Order By: Relevance
“…Pevonedistat inhibits all cullin-based E3 ligases and additionally exhibits cullin-independent activity (28,29,(63)(64)(65)(66)(67). However, the results described above suggest that the radiosensitizing activity of pevonedistat is due to its ability to induce rereplication, which can be enhanced by IR.…”
Section: Induction Of Rereplication Via Cdt2 Depletion or Cdt1 Activacontrasting
confidence: 47%
See 1 more Smart Citation
“…Pevonedistat inhibits all cullin-based E3 ligases and additionally exhibits cullin-independent activity (28,29,(63)(64)(65)(66)(67). However, the results described above suggest that the radiosensitizing activity of pevonedistat is due to its ability to induce rereplication, which can be enhanced by IR.…”
Section: Induction Of Rereplication Via Cdt2 Depletion or Cdt1 Activacontrasting
confidence: 47%
“…This significant apoptotic response was attributed to the induction of c-FLIP degradation, which the authors showed to be independent of NEDD8 inhibition (67). Furthermore, it is now abundantly clear that hundereds of cellular proteins are regulated through neddylation, and consistently, pevonedistat inhibits several signal transduction pathways, including the NFkB, AKT, and the mTOR signaling pathways, in addition to cullin-signaling (28,29,(63)(64)(65)(66). Thus, pevonedistat may exhibit differential toxicities in HNSCC cells and tumors depending on the genetic backgrounds of the cells or tumors as well as on the concentrations employed.…”
Section: Discussionmentioning
confidence: 99%
“…In view of recent studies showing that MLN4924 induces apoptosis in a subset of lymphomas and in myeloma through mechanisms distinct from the Cdt1 upregulation and re-replication seen in solid tumor cells, 10,12 we examined the mechanism of MLN4924-induced cytotoxicity in AML cells. In initial experiments, HL-60, U937, and ML-1 cells were treated with 30-1000 nM MLN4924 for 4-48 h, concentrations and times routinely used for MLN4924 in in vitro assays.…”
Section: Mln4924mentioning
confidence: 99%
“…1,11 Other mechanisms of MLN4924-induced killing involving nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and Redd1 have been described in a subset of diffuse large B-cell lymphoma and multiple myeloma cells, respectively. 10,12 The dominant stabilized CRL substrate and downstream steps governing the mechanism of MLN4924 cytotoxicity in AML are not as well defined, although induction of apoptosis has been observed. 3,5 The 'intrinsic' or 'mitochondrial' apoptotic pathway is activated when Bax and Bak proteins oligomerize in the outer mitochondrial membrane and induce cytoplasmic translocation of cytochrome c, which promotes caspase 9 activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation